Dolnoodrzańska enklawa kultury ceramiki sznurowej w ramach circumbałtyckiego kręgu KCSZ - Matuszewska, Agnieszka (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The present project has taken two spatial dimensions: regional and pan-regional. As far the regional dimension is concerned, I focused on the region of the lower Oder river. The main objective of this project was to create the fundamentals of taxonomic-chronological systematics of Corded Ware Culture materials for this region as well as summarise and verify previous achievements of studies on the aforementioned issue. However, as regards the pan-regional dimension, I attempted at discussing this region against the background of a wider communicative community– the circum-Baltic circle of Corded Ware Culture.
The Lower Odra enclave of the Corded Ware Culture of the circum-Baltic circle of the CWC